A fighting chance - Warren, Elizabeth (New York Metropolitan Books/Henry Holt and Company, 2014)
A chronicle of the Massachusetts senator's two-decade career in Washington describes her childhood pursuit of an education, early exposure to the dysfunctional political process, high-risk advocacy of better bankruptcy laws and competitive run for public office
Includes bibliographical references (pages 279-336) and index
Keywords: Warren, Elizabeth; United States. -- Congress. -- Senate -- Biography; Women legislators -- United States -- Biography; Legislators -- United States -- Biography; United States -- Politics and government -- 2009-.; Electronic books